2006
DOI: 10.1590/s0104-42302006000300015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de sintomas urinários no terceiro trimestre da gestação

Abstract: In the population under study pregnancy per se was associated to a high prevalence of irritative bladder symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
2
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 23 publications
(33 reference statements)
3
16
2
5
Order By: Relevance
“…This ranks the severity of symptoms in four categories:. Mild (1-5 points), moderate (6)(7)(8)(9)(10)(11)(12), severe (13)(14)(15)(16)(17)(18), and severe (19)(20)(21). (11) In this study the overall average ICIQ-SF score was 9.9 points.…”
Section: Evaluation Of the Knowledge Of The Perineal Regionmentioning
confidence: 45%
See 2 more Smart Citations
“…This ranks the severity of symptoms in four categories:. Mild (1-5 points), moderate (6)(7)(8)(9)(10)(11)(12), severe (13)(14)(15)(16)(17)(18), and severe (19)(20)(21). (11) In this study the overall average ICIQ-SF score was 9.9 points.…”
Section: Evaluation Of the Knowledge Of The Perineal Regionmentioning
confidence: 45%
“…(23) Also observed the symptoms of urinary urgency in about 60% of pregnant women, and 23.3% had the symptom of urge incontinence. Scarpa et al (19) found the urgency in about 47% of pregnant women were multiparous and 39% of gilts. Urge incontinence was present in 19% of multiparous and 22% of gilts.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…There are few population studies in Brazil (4) , using different methodologies and in general addressing specific groups such as women during pregnancy or in distinct periods postpartum (10) , elderly individuals (11) or institutionalized chronic patients (12) , and patients in the postoperative phase of radical retropubic prostatectomy; this last group has an incidence of 62% of UI in 13 studied patients (13) . These facts confirm the need and relevance of this study (13) .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, hormonal changes, occurred mainly from the second trimester of pregnancy, may cause changes in the connective tissues, influencing the support and continence mechanism 1 . As a result of these changes, there may be a reduction in support of the bladder neck and proximal urethra, predisposing pelvic floor (PF) dysfunctions 2,3 , which may become more prevalent as the pregnancy progresses and are associated with the pressure exerted by the fetal head on the bladder 4,5 . O'Boyle et al 6 observed a significant increase in urethral mobility in primigravidae, suggesting that physiological changes occur in the pelvic floor (PF) during pregnancy.…”
Section: Introductionmentioning
confidence: 99%